Associations for preschool environmental quality with outdoor time and moderate-to-vigorous physical activity in Norwegian preschools - Kjersti Johannessen; Elisabeth Bjørnestad; Ada Kristine Ofrim Nilsen; Einar Ylvisåker; Merete Nornes-Nymark; Mari Engeseter; Lillian Pedersen; Eivind Aadland (Cappelen Damm Akademisk NOASP, 2020)
Various aspects of the preschool environment may either promote or restrict children's moderate- to-vigorous physical activity (MVPA), for example through opportunities for outdoor play. The aim of the present study was to determine associations for preschool environmental quality with outdoor time and MVPA in preschoolers. In total, 358 Norwegian 2-6-year-old children had 1-3 valid 14-day periods of accelerometer-determined MVPA (ActiGraph GT3X+) and corresponding logs of preschool outdoor time collected during 2015-2016. The children were enrolled in 30 different preschool departments for which we assessed environmental quality using the Early Childhood Environment Rating Scale-Revised (ECERS-R). Associations for preschool quality with outdoor time and MVPA were determined using multivariate pattern analysis. We found strong inverse associations between preschool quality and outdoor time (51.4 % explained variance), and weak inverse associations between preschool quality and MVPA (5.4 % explained variance). Associations were strongest for the "Space and Furnishings", "Personal Care Routines", "Language-Reasoning", and "Interaction" subscales of ECERS-R, in particular for aspects of safety practices. Children enrolled in departments rated as high quality spent less time outdoors and less time in MVPA. Thus, recognized quality aspects of preschool environments, in particular safety practices, might restrict children's movement opportunities.